DETEKSI Staphylococcus aureus Methicilin-Resistant (MRSA) PADA ISOLAT INFEKSI LUKA OPERASI (ILO) PASIEN PASCA BEDAH ORTHOPEDI RSUD KRATON PEKALONGAN - Mulia Susanti; Dista Hanan (LPPM Universitas Abdurrab, 2026)
Surgical Site Infection (SSI) is a post-surgical complication that can increase patient morbidity, mortality, and length of hospital stay. One of the causative bacteria of SSI is Methicillin-resistant Staphylococcus aureus (MRSA), which exhibits resistance to β-lactam antibiotics. This study aimed to detect MRSA bacteria in SSI among post-orthopedic surgery patients at RSUD Kraton Pekalongan. This exploratory descriptive study employed a convenience sampling technique. The research samples consisted of three bacterial isolates obtained from post-orthopedic surgery patients with SSI. MRSA identification was performed through bacterial culture, Gram staining, biochemical testing, and antibiotic sensitivity testing utilizing the BD Phoenix automated system based on the Minimum Inhibitory Concentration (MIC) values, interpreted according to the 2024 CLSI guidelines. The results showed that all examined isolates (3/3; 100%) were identified as Methicillin-resistant Staphylococcus aureus (MRSA). In conclusion, all bacterial isolates obtained from orthopedic postoperative SSI patients included in this study were identified as MRSA.